Actividades De Control Previo Al Pago De Provedores Del Gobierno Autónomo Descentralizado Municipal Del Cantón San Francisco De Puebloviejo - Carrasco León, Thalía Carla (2018)
The Internal Control Standards are established by the Office of the Comptroller General of the State for public institutions in order to promote and guarantee the correct use of the funds, goods and public resources; as well as in Public Institutions and Institutions Private who have public resources, they must carry out the Control processes Internal as established by the norm, since it is a commitment of the highest authority, supervisors and other public servants and servants carry out the impeccable management of processes, payments and transfers made in these institutions. Internal control is the responsibility of all levels and all functions, The Charter Suprema clarifies that all servants and public servants will be responsible for all their acts carried out in the exercise of their functions. (Constitution of the Republic of Ecuador Article 233, 2008, p.81). The requirement of Internal control is clearly manifested, given that in the GAD Municipal del Cantón San Francisco de Puebloviejo avoids that responsibility for the majority of the servers and servants in implementing actions or procedures for the management of a correct internal control, and this is reflected when making payments or transfers to said suppliers, the lack of supporting documentation for payments causes delays and interruption of works, inefficiency in the attention to the citizenship, conflicts between the servers public